2017
DOI: 10.29328/journal.jpsp.1001004
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic features displayed by Plant Growth Promoting Rhizobacteria (PGPR): A Review

Abstract: Soil dwelling bacteria able to colonize plant roots and closely associated soil are referred to as rhizobacteria. A wide range of rhizobacteria has the ability to promote plant growth directly by producing phytohormone and nutrients; and indirectly by controlling plant pathogen. These benefi cial bacteria are known as plant growth promoting rhizobacteria (PGPR). PGPR control phytopathogens by producing chemicals that could damage pathogen cells, removing pathogen specifi c nutrients from the environment, or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…These PGPR can affect plant growth and development in different ways. In general, PGPR promote plant growth directly by increasing nutrient acquisition (N, P, K, and essential minerals) or by regulating plant hormone levels, or indirectly, by reducing the inhibitory effects of various pathogens on plant growth and development in the form of biological control agents (Tariq et al, 2017). PGPR also clean the environment by detoxifying pollutants such as heavy metals and pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…These PGPR can affect plant growth and development in different ways. In general, PGPR promote plant growth directly by increasing nutrient acquisition (N, P, K, and essential minerals) or by regulating plant hormone levels, or indirectly, by reducing the inhibitory effects of various pathogens on plant growth and development in the form of biological control agents (Tariq et al, 2017). PGPR also clean the environment by detoxifying pollutants such as heavy metals and pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…Both subtilisin-like protein forms were also present in peak 2, even if with a lower concentration, together with a B-glucanase, whereas peak 3 contains a metalloprotease and an alpha-amylase. Since serine-proteases, Beta-glucanase and glucoronoxylanase were demonstrated to act as antifungal agents [18,19], our results suggested that the activity of these secreted molecules could be responsible, at least partially, of the antifungal action of RHFS10. To further corroborate this hypothesis, a mass spectrometry-based proteomic analysis on the previously described 72-CFSs of RHFS10 strain treated at increasing temperatures (cfr.…”
Section: Preliminary Identification Of Bioactive Compoundmentioning
confidence: 76%
“…This increase was due to the physiological activity of bacteria in the bionematicide formula (Mehmood et al 2018). Tariq et al (2017) reported that rhizobacteria had dual roles as plant protector agent and plant growth promoter. In a separate study, Afzal et al (2019) also reported that endophytic bacteria could induce plant growth.…”
Section: Discussionmentioning
confidence: 99%